Analysis of sprint ski mountaineering performance - Fornasiero, A.; Fornoni, S.; Callovini, A.; Todesco, B.; Savoldelli, A.; Schena, F.; Holmberg, H.-C.; Pellegrini, B.; Bortolan, L. (International Journal of Sports Physiology and Performance, 2023)
Ski mountaineering sprint competitions are short individual races involving 3 uphill sections (U), 3 transitions (T), and a final descent. To date, relatively little is known about this novel Olympic discipline, and here we examined (1) the contribution of the time spent on U, T, and final descent to overall finishing time and (2) the potential relationships with final ranking. During the different rounds of 2 International Ski Mountaineering Federation World Cup sprint competitions, male and female ski mountaineers were video recorded. Correlation and multiple linear regression analyses were used to investigate the impact of U, T, and final descent on the best overall finishing time. Linear-mixed model analysis was applied to explore potential interactions between section times, rounds, and final ranking. Overall, U (r = .90-.97) and T (r = .57-.89) were closely correlated with the best overall finishing time (all P < .05). U explained approximately 80% to 90% of the variation in the best finishing time for both sexes, with U + T explaining approximately 95% to 98% of this variation. In each successive round, the ski mountaineers eliminated were all slower on U than the Top 3 (all P < .05). The fastest skiers increased their performance on U in the later rounds of the competitions, while those eliminated showed a tendency toward a decrease. Our findings reveal that world-class sprint ski mountaineers conduct transitions optimally and perform effectively uphill. Training for such competitions should aim to improve short supramaximal uphill performance (~1.5-2.5 min), ensuring that this does not decline with multiple efforts. These insights into ski mountaineering sprint performance are of considerable value in connection with training for the 2026 Winter Olympics.